2004
DOI: 10.1128/jcm.42.11.5015-5021.2004
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association between Genotype F and Hepatitis B Virus (HBV) e Antigen-Negative Variants among HBV-Infected Argentinean Blood Donors

Abstract: A number of reports have indicated an increased risk of cirrhosis and hepatocellular carcinoma in hepatitis B virus (HBV)-infected individuals carrying HBV e antigen (HBeAg)-negative variants. Although distinct core promoter and precore mutations distributed according to geographical locality and viral genotype have been reported, epidemiological data from South America are still scarce. The prevalences of HBV genotypes and core promoter and precore polymorphisms in 75 HBeAg-negative Argentinean blood donors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 64 publications
4
31
0
Order By: Relevance
“…Several molecular epidemiology studies of HBV carried out in Argentina and performed with African descendants in Venezuela and Brazil have never detected the circulation of HBV genotype E (19,9,8,16,7,15,3,10). This could imply that the emergence of this genotype among humans was a late event that occurred following the introduction of slaves into the Americas (i.e., after the 15th century).…”
mentioning
confidence: 99%
“…Several molecular epidemiology studies of HBV carried out in Argentina and performed with African descendants in Venezuela and Brazil have never detected the circulation of HBV genotype E (19,9,8,16,7,15,3,10). This could imply that the emergence of this genotype among humans was a late event that occurred following the introduction of slaves into the Americas (i.e., after the 15th century).…”
mentioning
confidence: 99%
“…In contrast, patients who contracted the disease later in life are less likely to suffer serious sequelae (only~20% develop cirrhosis or HCC) since their disease has had a relatively shorter time to progress. Despite geographic differences in genotypes and in the prevalence of HBeAg-positive and -negative disease [16][17][18][19][20] (Table 1), clinicians worldwide are now more likely to encounter patients of all genotypes and both HBeAg-positive and -negative disease during their practice as a result of population migration, and consequently need to know how to treat all types of patient appropriately.…”
Section: Burden Of Diseasementioning
confidence: 99%
“…Genotype A infection was associated with a better response (52%) compared to genotypes B (30%), C (31%) and D (22%). Long-term sustained HBeAg-seroconversion was associated with substantial HBV DNA reduction and ALT normalisation, with 72% of patients having HBV DNA [16][17][18][19][20] levels <10,000 copies/ml (~2,000 IU/ml) and 82% having normal ALT 1 year post-treatment. Studies of pegylated interferon alfa-2b with or without lamivudine for 1 year found that 35% of subjects had lost HBeAg at follow up; that there was no benefit from the addition of lamivudine; and that genotype A subjects had a better response [34].…”
Section: Pegylated Interferonmentioning
confidence: 99%
“…There is a high prevalence of genotypes A and D as a reflection of the migratory movements that occurred during the colonial period, especially subtype A1, related to the slave trade [31,32], and A2 and several subtypes of genotype D, associated with European settlers. Strains of genotypes B and C have been isolated in Peru and Panama, as well as in Argentina and Brazil [33][34][35]. Genotypes A, H and G have been detected in Mexico, while genotypes A and H have been found in Nicaragua.…”
Section: Introductionmentioning
confidence: 99%